2003
DOI: 10.1081/jlc-120017181
|View full text |Cite
|
Sign up to set email alerts
|

Validation of HPLC Determination of Phenolic Acids Present in Some Lamiaceae Family Plants

Abstract: HPLC columns with different length, particle size, and chemical properties of sorbent were tested and compared for the application in the development of the universal HPLC assay for determination of phenolic compounds, which could be present in some medicinal plants from the Lamiaceae family (Melissa officinalis, Rosmarinus officinalis, Salvia officinalis, Thymus serpyllum, and Origanum vulgare). More RP-18 columns have been chosen for the simultaneous separation of all phenolic compounds in the study. The bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 5 publications
0
25
0
1
Order By: Relevance
“…High amounts of total phenolics and RA were extracted with both methods of drying, showing there was no difference between freeze dry and oven dry to extract total phenolics and RA in Italian large leaf basil (Table II). reported that rosmarinic acid is the most abundant phenolic compound in other aromatics plants such as Salvia officinalis (19,22,57), Melissa officinalis (12,19), Thymus vulgaris, Rosmarinus officinalis (19), Origanum x majoricum (22), Origanum vulgare (5,19), Satureja montana (5). (Table III).…”
Section: Effect Of Different Methods Of Processing Rosmarinic Acid Comentioning
confidence: 95%
“…High amounts of total phenolics and RA were extracted with both methods of drying, showing there was no difference between freeze dry and oven dry to extract total phenolics and RA in Italian large leaf basil (Table II). reported that rosmarinic acid is the most abundant phenolic compound in other aromatics plants such as Salvia officinalis (19,22,57), Melissa officinalis (12,19), Thymus vulgaris, Rosmarinus officinalis (19), Origanum x majoricum (22), Origanum vulgare (5,19), Satureja montana (5). (Table III).…”
Section: Effect Of Different Methods Of Processing Rosmarinic Acid Comentioning
confidence: 95%
“…Rosmarinic acid was the most abundant phenolic compound present in the decoctions; many authors have also reported this compound as the main phenolic compound in this species. 3,24,26,[28][29][30] Luteolin derivatives have also been reported as relevant phenolics in M. officinalis, 3,23,25,28,30 but this type of derivatives (with low hydrophilicity) was absent in the decoction of M. officinalis. Rosmarinic acid has been reported as displaying high antioxidant and antibacterial activity.…”
Section: View Article Onlinementioning
confidence: 99%
“…Caffeic acid and gallic acid are naturally found in the majority of herbs and are present in the free form or commonly bound as esters, depsides, and/or glycosides. Rosmarinic acid is a typical active compound of sage, marjoram, oregano and other herbs; (+)-catechin is free or as an ester mainly with gallic acid (Ziaková & Brandšteterová 2003;Yanishlieva et al 2006;Kivilompolo & Hyötyläinen 2007;Kulisic et al 2007;Velíšek 2009 etc. ).…”
Section: Determination Of Antioxidant Capacity Of Extractsmentioning
confidence: 99%